Patient satisfaction with maxillofacial prosthesis. Literature review - Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP]; da Silva, Cristina Ramos [UNESP]; Gennari Filho, Humberto [UNESP]; Santos, Daniela Micheline dos [UNESP] (Elsevier B.V., 2009)
Obturators and facial prostheses are important not only in rehabilitation and aesthetics, but also in patient re-socialisation. The level of reintegration is directly related to the degree of satisfaction with rehabilitation. So, the maxillofacial prosthetics must provide patient satisfaction during treatment. This study aimed to search information in database and conduct a literature review on patient satisfaction with maxillofacial prosthesis. The problems experienced by these patients may decrease when specialists keep the patient on regular inspection. Rehabilitation through alloplasty or prosthetic restoration provides satisfactory conditions in aesthetics and well-being and reinstates individuals in familial and social environment. (C) 2008 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Maxillofacial prosthesis; Patient satisfaction; Obturator maxillary